Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT.Semen Indonesia (Persero) Unit Tonasa Kabupaten Pangkep - Syah, Nur Fiqri; Nurman, Nurman; Ruma, Zainal; Sahabuddin, Romansyah; Burhanuddin, Burhanuddin (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
This study aims to determine the effect of compensation and work environment on performance at PT. Semen Indonesia (Persero) Tonasa Unit, Pangkep Regency. This type of research is quantitative. The population of this study are employees of PT. Semen Indonesia (Persero) Tonasa unit, Pangkep Regency, part of the manager, totaling 134 people. And the sample in this study were 100 people. The data collection technique used is in the form of primary data by distributing and filling out questionnaires. The data analysis technique used is multiple linear analysis using the Statistical Product Service Solution (SPSS). The results of this research show that the compensation variable (X1) partially has a significant positive effect on employee performance (Y) with t count > t table which is 6.924 > t table of 1.984. The work environment variable (X2) has a significant positive effect on employee performance (Y) with t count > t table where 2.296 > t table of 1.984. Based on the results of this research, it is also known that the independent variables together or simultaneously have a significant effect on the dependent variable, namely employee performance at PT. Semen Indonesia (Persero) Tonasa unit, Pangkep Regency. Therefore, if compensation and work environment continue to be improved, it will certainly improve employee performance.